PARASIT PADA BELUT SAWAH ( Monopterus albus, Zuiew 1793 ) DI DESA SAWAH KECAMATAN KAMPAR UTARA - Syauli Ashari Khati; Radith Mahatma; WIndarti ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Monopterus albus, Zuiew 1793 (Synbranchidae) or swamp eel is rich in proteinand commonly used in Riau’s culinary. It is easily found in muddy areas, ricepaddy fields and in the organic material polluted area where this fish is able totolerate to the polluted environment. Fish living in the organic polluted area mayface the risk of parasite infection, including the zoonotic parasite that may infecthuman being. To understand the parasite present in swamp eel, a study had beenconducted. The study area of this research was a domestic polluted swamp area inthe Sawah Village (Kampar Regency Riau). Thirty eels from this area were usedfor parasite identification study. Results showed that among the samples, 14 fisheswere infected by nematode parasite Gnathostoma spp. This parasites were presentin the gonad, liver, body wall and peritoneum. The parasites were found in 5developmental stages namely egg, 1 st , 2 nd , 3 rd and 4 th larvae.